UPAYA MENINGKATKAN PENGELOLAAN DIRI DALAM BELAJAR MELALUI LAYANAN PENGUASAAN KONTEN PADA SISWA KELAS IX-3 SMP NEGERI 7 MEDAN TAHUN AJARAN 2017/2018 - Marintan Manurung (Universitas Islam Negeri (UIN) Sumatera Utara, 2020)
The purpose of this study was to determine the implementation of effective content mastery services to improve self-management in student learning. This type of research is the PTK BK. The research subjects were 32 students of class IX-3 SMP Negeri 7 Medan. Data collection methods are interviews and observation. The results of the study were obtained before getting content mastery service, namely 49% with low criteria with details of 14 students, and 51% with moderate criteria with details of 18 students. After giving the action cycle 1, namely 17.14% with the low category with details of 6 students, 65.72% with the medium category with details of 23 students and 17.14% with high criteria with details of 6 students. The percentage after cycle 2 was 82.8% with the medium category with details of 23 students and 17.14% in the high category with details of 6 students.